Enhancing Thai Learners’ Morphological Awareness of English Words through Activity-Based Learning - Paicharoen, Narisa (Journal of Arts and Thai Studies, 2024)
Objectives: The purposes of this research were: 1) to examine Thai learners’ morphological awareness of English words before and after implementing activity-based learning, based on a comparison with the 60 percent criterion, and 2) to explore the attitudes of Thai learners towards activity-based learning. Methods: The target group consists of 11 English major students enrolled in 146265 Morphology and Syntax course during the first semester of the 2022 academic year. The research tools include the morphological awareness pre-test and post-test divided into two parts: 1) morpheme segmentation, and 2) sentence completion with derivational and inflectional affixes. Lesson plans including activities to promote morphological awareness, reflective journal, and a questionnaire to assess learners’ attitudes were also employed as research instruments. Statistics used include percentages, means, and standard deviations. Results: When considering the pre-test scores, it was found that the overall average scores of the target group did not meet the 60 percent criterion. For the post-test scores, it was revealed that scores for part 1 of the test met the 60 percent criterion, whereas scores for part 2 did not meet the criterion. Regarding learners’ attitude towards activity-based learning, it was generally found that they were at a high level. In addition, the result from reflective journals revealed their positive viewpoints and feeling about activity-based learning. Application of this study: Learning activities employed in this research can be applied in Morphology course for other languages such as French, Chinese, or Japanese.